Studying of the biological characteristics of vetiver - Vetiveria zizanioides (L.) Nash in Thua Thien - Hue province - Tri, Nguyen Minh; Loc, Nguyen Ba; Thang, Nguyen Viet (Academia Journal of Biology, 2012)
Vetiver grass has been the Ministry of Agriculture Rural Development and Ministry of Transportation allowed in the country to protect infrastructure from 2003. In Thua Thien - Hue also tested vetiver grass planted since 2005 to prevent hole in some rivers such as the Huong river, Bo river.... With the characteristics of plant morphology and physiological - biochemical characteristics research has showed that vetiver grass has high adaptability in different areas, they have grown, developed and used to counter soil erosion and landslides in Thua Thien - Hue province. Leaves of vetiver grass were used as feed for cattle due to high levels of nutrients. Seeds of vetiver grass not germinating in natural conditions should not widely distributed, this species breeding primarily in the form by budding from the mother plant is so safe on environmental issues.